MAIN TYPES OF ROTATING MECHANISMS AND THEIR COMMON FAULTS - Utkirjon, Ubaydullayev; Rakhmanova, Elmira (Research Focus International Scientific Journal, 2026)
This article analyzes the main types of rotating mechanisms widely used in industry, transport, energy, and household appliances, including their operational characteristics and the most common faults encountered during operation. Rotating assemblies are the heart of nearly every complex technical system, and their reliable performance is directly linked to production continuity, energy efficiency, and safety. The paper provides a systematic overview of shafts and rotors, bearing supports, gear drives, couplings, rotating components of pumps and fans as well as rotor systems of electrical machines. Furthermore, the causes, symptoms, and prevention methods of imbalance, misalignment, bearing wear, lubrication system defects, gear set damage flow-related failures, and electromechanical issues are discussed from a scientific and practical perspective.